Problem of Fuzzy portfolio optimization and its solution with application of forecasting methods - Zaychenko, Y.; Sydoruk, I. (Системні дослідження та інформаційні технології, 2016)
The novel theory of investment portfolio optimization under uncertainty is presented based on fuzzy set theory and efficient forecasting methods. The direct problem of fuzzy portfolio optimization and dual problem are considered. In the direct problem structure of a portfolio is determined which provides the maximum profitableness at the given risk level. In dual problem the portfolio structure is determined which provides the minimum risk level at the set level of critical profitableness. For estimation of stocks profitableness in future moment the application of forecasting method- Fuzzy Group Method of Data Handling (FGMDH) is suggested. This method enables to construct fuzzy forecasting models by experimental data almost automatically. The experimental investigations of the suggested theory were carried out and comparison with classical portfolio model was performed. Подано нову теорію портфельної оптимізації в умовах невизначеності, що ґрунтується на застосуванні теорії нечітких множин та ефективного методу прогнозування. Розглянуто пряму та двійкову задачі нечіткої портфельної оптимізації. У прямій задачі визначається структура оптимального портфеля цінних паперів, яка забезпечує максимум очікуваної дохідності при обмеженнях на ризик, у двійковій задачі – структура портфеля, який забезпечує мінімум ризику при обмеженнях на встановлений рівень критичної дохідності. Для визначення дохідності цінних паперів запропоновано метод прогнозування нечіткого методу врахування аргумента, що дозволить будувати нечіткі прогнозні моделі за експериментальними даними автоматично за незначної участі експерта. Описано експериментальні дослідження запропонованої теорії та проведено порівняння з класичною моделлю портфельної оптимізації. Представлена новая теория портфельной оптимизации в условиях неопределенности, базирующая на применении теории нечетких множеств и эффективного метода прогнозирования. Рассмотрены прямая и двойственная задачи нечеткой портфельной оптимизации. В прямой задаче определяется структура оптимального портфеля ценных бумаг, обеспечивающая максимум ожидаемой доходности при ограничениях на риск, в двойственной задаче — структура портфеля, обеспечивающая минимум риска при установленном уровне критической доходности. Для определения доходности ценных бумаг предложен метод прогнозирования — нечеткий метод группового учета аргументов, позволяющий строить нечеткие прогнозные модели по экспериментальным данным автоматически при минимальном участии эксперта. Описаны экспериментальные исследования предложенной теории и проведено сравнение с классической моделью портфельной оптимизации.